The Use of "Asset Swaps" by Institutional Investors in South Africa - Dimitri Vittas (World Bank, Washington, DC, 2014)
Leading financial economists have proposed the use of international asset swaps (Merton 1990, Bodie and Merton 2002) as a way of efficiently achieving international diversification without eroding the level of foreign exchange reserves and weakening local market development. International asset swaps entail limited foreign currency flows (only net gains or losses need to be exchanged). They protect foreign investors from market manipulation and expropriation risk and have much lower transaction costs than outright investments. But asset swaps are constrained by the attractiveness of local markets to foreign investors, and by various regulatory issues covering counterparty risk and collateral considerations, and accounting, valuation, and reporting rules. Institutional investors are well developed in South Africa. Their total assets corresponded in 2001 to 159 percent of GDP, a level that was surpassed by only four high-income countries. But because of the imposition of exchange controls, they lacked international diversification. In July 1995 South Africa was the first developing country that explicitly allowed its pension funds and other institutional investors to make use of "asset swaps." But the South African authorities did not authorize the use of properly specified swap contracts as described by Bodie and Merton, but rather permitted institutional investors to "obtain foreign investments by way of swap arrangements." As the author argues in this paper, the asset swap mechanism turned out to be cumbersome and inefficient. However, it did allow institutional investors to attain some level of international diversification. Other developing countries should consider authorizing their institutional investors to engage in international asset swaps. But they should authorize the use of properly designed swap contracts, preferably based on baskets of liquid securities, permit only global investment banks to act as counterparties, require the use of global custodians, properly monitor credit risk, maintain adequate collateral, and adopt market-to-market valuation rules. Asset swaps are clearly a second-best option compared to the lifting of exchange controls. However, they may facilitate risk diversification in the presence of such controls. And they may even have a role to play in their absence.